Without Criteria: Art and Learning and the Adventure of Pedagogy. (27th June 2016) - Atkinson, Dennis
Abstract: A key aim of this article is to present a discursus on learning and teaching in the context of art education that softens transcendent historical and ideological framings of art education and its purpose. In contrast it places emphasis upon the immanence and necessary transcendence of local events of learning that occur in whatever framing and which have the potential to extend our comprehension of what art and learning can become. It recommends a 'pedagogical reversal' whereby external transcendent lenses and their respective knowledge and criteria for practice are relaxed and proposes a pedagogy 'without criteria'. A key pedagogical issue revolves around 'how something matters' for a learner in his or her experience of a learning encounter and trying to comprehend this 'mattering' constitutes a pedagogical adventure for a teacher. The notion of mattering in the context of art practice and learning cannot be divorced from the force of art which is the motive force that precipitates a potential for learning and can expand our understanding of what art and learning can become. The article is therefore premised on the idea that it is not a case of coming to understand art through established knowledge and practice but the force of art challenging us to think. The force of art, or art's event, can be conceived therefore as a process with a potential for the individuation of new worlds or to see that other worlds might be possible.